PSoC based water quality monitoring system - Wong, Zhen Cong. (2011)
Water is a limited resource and is essential for agriculture and industrial use, especially fresh water which is sacred. Water quality monitoring is important for both human and environmental. By keeping track of contaminants, we can determine whether the water is fit for consumption or even be dangerous to plants and animals. Apart from contaminants, unaccounted-for-water (UFW) is another important area to monitor. UFW could be caused by leaks, inaccurate metering, unauthorized usage and other cases. Singapore has a low UFW rate of less than 5% comparing to more than 30% in other countries older distribution network.